Effect of essential oils from Cymbopogon citratus, Citrus grandis, and Mentha arvensis on Trichomonas vaginalis and role of its symbionts Mycoplasma hominis and Ca. Mycoplasma girerdii - Margarita, Valentina; Nguyen, Thi Ha Trinh; Petretto, Giacomo Luigi; Congiargiu, Antonella; Ligas, Antonietta; Diaz, Nicia; Ton Nu, Phuong Anh; Pintore, Giorgio; Rappelli, Paola (Frontiers in Parasitology, 2025)
IntroductionTrichomoniasis, the most common non-viral sexually transmitted disease, is caused by the protozoon Trichomonas vaginalis. T. vaginalis can establish a symbiosis with two bacteria, Mycoplasma hominis and Candidatus Mycoplasma girerdii, whose intracellular presence may modulate several characteristics of the protozoan, including its sensitivity to 5-nitroimidazoles, the only class of drugs currently effective in treating trichomoniasis. The rising prevalence of T.vaginalis strains resistant to metronidazole, the most commonly used antitrichomonal drug, underscores the need for therapeutic alternatives active against the protozoon.MethodsIn this study, we evaluate the antimicrobial activity of essential oils extracted from three plants cultivated in Vietnam — Cymbopogon citratus, Citrus grandis, and Mentha arvensis — against thirty T. vaginalis strains isolated from symptomatic women in Italy and Vietnam. We also assess the influence of M. hominis and Ca. M. girerdii on T. vaginalis susceptibility to essential oils and metronidazole, through dedicated susceptibility assays. Additionally, given the importance of lactobacilli in maintaining vaginal health, we investigate the effects of the essential oils on Lactobacillus gasseri and Lactobacillus crispatus. The cytotoxic activity of the oils against HeLa cells was also tested in vitro.ResultsAll three essential oils showed effective antitrichomonal activity without inhibiting lactobacilli growth. Among them, C. citratus oil exhibited the strongest inhibitory effect on T. vaginalis, including strains harboring bacterial symbionts. Moreover, the oils demonstrated no cytotoxic activity against HeLa cells at the concentrations effective against the protozoan.DiscussionThe results support the potential of C. citratus essential oil as a natural antitrichomonal agent. Its effectiveness against both free and symbiont-infected T. vaginalis strains positions it as a promising candidate for developing alternative therapies against drug-resistant trichomoniasis.